The application of continuous integration and test methodologies to rotorcraft HUMS - Dunning, P.; Nowik, M.; Nyczkowski, L.; Mead, C. (My University, 2019)
Continuous Integration and Test (CIT) is a mature technique used to support Agile software development practices and it has seen increasing adoption for avionics software development over the last 10 - 15 years. However, point solutions are usually adopted for avionics CIT as standard frameworks for implementing it do not exist. Test PASS, developed by The Warsaw Institute of Aviation (WIA) in collaboration with General Electric Company Polska (GECP) is proposed as a framework for CIT in an embedded, safety critical environment. Its application to GE’s next generation HUMS is described as a challenging use case that fully demonstrates the framework’s flexibility and capabilities. The challenges of implementing a CIT approach for HUMS are presented as are the solutions enabled by Test PASS. The benefits to the GE’s next generation HUMS product including improved robustness and development effort efficiencies are described.